Enhancing Kindergarteners’ English Vocabulary and Pronunciation through Morning Circle Activities - Wardhana, Edward Eka; Astutik, Yuli; Fediyanto, Niko; bte Abd Wahid, Nur Farhana (Journal of Nusantara Education, 2026)
This study investigates the implementation of Morning Circle as a strategic approach to enhance English vocabulary and pronunciation among kindergarten students. Grounded in Lev Vygotsky’s Zone of Proximal Development (ZPD) and the concept of scaffolding, this study explores how teacher–student interactions within this activity support early language acquisition. A descriptive qualitative method was employed through classroom observations conducted over six weeks in a kindergarten that routinely integrates Morning Circle into its English language learning practices. Data were collected through non-participant observations involving 23 students and one teacher, focusing on four main components: greetings, singing, counting, and material delivery. The data were analyzed thematically by identifying recurring patterns of teacher support and students’ language responses in relation to the ZPD framework. The findings reveal that each component of Morning Circle contributes significantly to language development. Greeting sessions provide structured exposure to basic English expressions with bilingual support. Singing integrates vocabulary with rhythm and movement, facilitating pronunciation practice. Counting activities reinforce number vocabulary while encouraging peer interaction. Material delivery emphasizes thematic vocabulary supported by modeling, gestures, and simplified explanations. Consistent use of scaffolding strategies, including modeling, repetition, bilingual cues, and physical demonstrations, plays a crucial role in guiding student engagement and linguistic progress. These findings suggest that Morning Circle, when purposefully designed, serves as an effective and developmentally appropriate framework for introducing foundational English skills. Beyond a daily routine, it functions as an interactive and intentional learning opportunity that supports vocabulary acquisition and pronunciation development